PENGARUH SISTEM PENGENDALIAN MANAJEMEN DAN KECERDASAN EMOSIONAL TERHADAP KINERJA STAFF ATC DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL PEMODERASI (Studi Kasus pada Perum LPPNPI AirNav Indonesia) - Anjumi, Fathul Huda; Yaya, Rizal (Riset Akuntansi dan Keuangan Indonesia, 2016)
The objective of this study is to analyze the effect of management control system and emotional intelligence on the performance of Air Traffic Controller (ATC) staffs with locus of control as a moderating variabel. This analysis used management control system and emotional intelligence as independent variables. The dependent variable is Performance of Air Traffic Controller. The samples used in this research are58 ATC staff with minimum education of Diploma 1 which was surveyed between 24 September to 5 November 2015. The statistical method used in this study is moderating regression analysis for the statistical test of hypothesis testing and statistical t test.Based on the analysis ofquestionnaires obtainedfound that the emotional intelligence hasa positive and significant impact on performance, while management control system does not have a significant effect on performance. Meanwhile in the statistical test by using locus of control as moderating variable, all independent variables have positive and significant influence.